Pt Vale Indonesia, Tbk: Evaluation Of Asset, Equity, And Liability Performance For Sustainable Growth - Agusalim Sunusi; Sukmawati Sultan Sahrir (Economics and Digital Business Review, 2024)
This study aims to analyze the financial performance of PT Vale Indonesia Tbk during the period from 2014 to 2023, focusing on asset growth, liability management, and operational efficiency amid commodity price volatility. This research is descriptive-evaluative, using the company's annual financial reports, which include financial figures, accounting notes, and additional information on policies, risks, and factors influencing the company's performance. The analysis results show fluctuations in the company's revenue during the period, but PT Vale managed to recover and experience positive growth, especially during the 2021-2023 period. Significant asset growth between 2021 and 2023 reflects the success of investments and acquisitions that improved production capacity and operational efficiency. The increase in Gross Profit Margin (GPM) reflects successful pricing strategies and operational efficiency, while the stability of non-current assets indicates the company's commitment to long-term investments. Strong growth in current assets also indicates good liquidity. Furthermore, careful liability management is reflected in a healthy Debt to Equity Ratio (DER), supporting the company's financial stability. Although liabilities increased during the recovery phase (2021-2023), the debt ratio remained controlled, and the company's equity grew. The company's liquidity indicators are also solid, with a high Current Ratio, although the company needs to improve the efficiency of current asset utilization. Improvements in Inventory Turnover and Receivable Turnover indicate effective management of inventory and receivables, which support cash flow and profitability. This study's recommendations include several strategic steps that PT Vale could take. The company should explore the use of digital technology to improve operational efficiency and inventory management. Further research is also needed to develop strategies for investing in current assets to optimize the use of idle funds. Additionally, focus should be placed on managing production and distribution costs to maintain or improve GPM. Although the Debt to Equity Ratio indicates a healthy condition, an evaluation of more efficient debt financing should be conducted to support business expansion without increasing financial risks. Finally, analyzing the impact of commodity price fluctuations and government policy changes on company performance could provide additional insights to strengthen strategic planning and risk mitigation.